Association between the C-reactive protein-triglyceride–glucose index and endometriosis: a cross-sectional study using data from the national health and nutrition examination survey, 1996–2006 - Yanan Ren; Ren Xu; Junqin Zhang; Ying Jin; Di Zhang; Yazhuo Wang; Luyang Su (BMC Women's Health)
Abstract Background The C-reactive protein–triglyceride glucose index (CTI) is a promising new marker for evaluating the severity of inflammation. Endometriosis (EM) is a prevalent chronic inflammatory condition influenced by estrogen, primarily affecting women of reproductive age. However, no study has demonstrated an association between the CTI and EM. Methods This cross-sectional study sourced data from females 20–50 years of age from the National Health and Nutrition Examination Survey (NHANES) 1996–2006, and included those with self-reported diagnoses of EM and sufficient information to calculate the CTI, computed as 0.412 × ln (C-reactive protein [CRP]) + ln (triglycerides [mg/dL] × fasting plasma glucose [mg/dL]/2). Multivariate logistic regression, restricted cubic splines, and subgroup analyses were performed to examine the association between the CTI and EM. Results Data from 2235 women (175 [7.82%] with EM, 2060 [92.18%] without EM [controls]), were included: those with EM exhibited a tendency toward higher CTI (p = 0.005), and CTI was positively associated with the prevalence of EM (p = 0.011). In Model 1, a 1 mg/dL increment in CTI was associated with a 56% higher prevalence of EM (odds ratio [OR] 1.563 [95% confidence interval (CI) 1.295–1.885]; P < 0.001). This association in Model 2 (OR 1.609 [95% CI 1.334–1.941]; p < 0.001) and Model 3 (OR 1.565 [95% CI 1.246–1.966]; p < 0.001) remained significant. Notably, individuals in the uppermost remnant cholesterol tertile exhibited a notably higher prevalence of EM than those in the lowest tertile (OR 3.029, p = 0.051). Restricted cubic splines revealed a nonlinear positive association between CTI and the prevalence of EM. In addition, greater EM prevalence was observed with CTI in those > 40 years of age (OR 1.57 [95% CI 1.16–2.13]), body mass index ≥ 25 kg/m2 (OR 1.38 [95% CI 1.06–1.80]), smoking ≥ 100 cigarettes (OR 1.43 [95% CI 1.06–1.96]), married or living with partner (OR 1.41 [95% CI 1.09–1.85]), and oral contraceptive use (OR 1.35 [95% CI 1.07–1.69]). Conclusions CTI was positively associated with EM in women in the United States. Use of the CTI as an indicator of inflammation may provide new insights for the prevention and management of EM.